Primary mucoepidermoid carcinoma of the trachea in a child - Papiashvilli, Michael (Oxford University Press, 2012)
Mucoepidermoid carcinoma of the trachea is a rare tumour, especially in the paediatric population. We report the case of a 9-year-old boy with mucoepidermoid carcinoma of the trachea that was preoperatively diagnosed as an intraluminal polypoid mass arising from the trachea and extending into the right main bronchus. A complete resection of the tumour with reconstruction and end-to-end anastomosis of the trachea was performed. The patient is now, 24 months after surgery, free of disease.